Urban solid waste and social-environmental impacts in the neighborhood of “Lagoa do Ferreiro”, Assu/RN - Andrade, Ayslann Todayochy Siqueira de; Alcântara, Roselene Lucena (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The demand to mitigate the problems caused by improper disposal of solid waste and the subsequent generation of social-environmental impacts has generated discussions and referrals in the search for alternative solutions, and this has caused problems for man. Therefore, this study aims to conduct a study to identify ways to dispose of solid waste in the city of Assú/RN and identify social and environmental impacts that affect the population of the neighborhood where the municipal dump is installed. For the development of the study, we used qualitative and quantitative research with interviews with representatives of municipal agencies responsible for municipal solid waste and a questionnaire with the garbage collectors. One of the major problems observed was the inadequate form of disposal of solid waste and the impacts generated by these in the population of the study object neighborhood, especially the garbage collectors that directly deal with waste. Due to the problems generated, sensitization/awareness campaigns are necessary with the population, to ensure better management of solid waste in the city, as well as the construction of a landfill for better management of municipal solid waste according to what has been established in the National Policy on Solid Waste (Federal Law 12.305/10).